Numeric methodology for determining the volumetric consumption of hydrated ethanol in flex-fuel vehicles - Shibuya, Marcelo K.; de Näas, Irenilza A.; Neto, Mario Mollo [UNESP] (Springer Nature, 2015)
The beginning of the manufacturing of the flex fuel vehicles in 2003, gave a new dynamic to fuel demand in Brazil. As the flex-fuel vehicles can be supplied with gasoline, hydrated ethanol or the mixture of the both in any proportion, the decision on which fuel to use occurs at the moment of supply, according to the most advantageous price and the consumer’s preference. Considering this scenario, the objective of the present study was to obtain a calculation method to determine the fuel volume used by the flex-fuel vehicle fleet. For this purpose, the fuel conversion in energy units of oil barrels was used. The fuel demand by type of vehicle was obtained through the proportion of the number of vehicles and the distance traveled in the period. The results indicate that there was a behavioral change on fuel consumption by the users of the flex fuel fleet.
Keywords: Ethanol; Flex-fuel vehicles; Fuel demand